Analysis of Preparation of Flight Coordinator Officers in Efforts to Achieve Ground Time for Transnusa Airbus A320 Aircraft at PT. Semesta Space Services Terminal 3 Soekarno Hatta Airport - Ramadhani, Sheny; Martanti, Ika Fathin Resti (CV. Rayyan Dwi Bharata, 2024)
Flight coordinator is the unit tasked with coordinating the implementation of aircraft handling. Flight coordinator officers play an important role in providing air services from block on to block off, therefore the potential for incidents and accidents in this area is higher compared to other areas. This research aims to analyze the preparation of flight coordinator officers in an effort to achieve ground time for the Transnusa Airbus A320 aircraft at PT Jasa Angkasa Semesta Terminal 3 Soekarno Hatta Airport. The research design used in this research is qualitative descriptive research using primary data (observations and interviews) and secondary data (library studies and documents). Data collection techniques are carried out by observation, playing a role in the field, interviews with Senior On Duty and personal flight coordinators, flight coordinator activity documents and library studies. Data analysis techniques are by collecting data, reducing data, presenting data and drawing conclusions. The research results showed that the flight coordinator officers had carried out their duties in accordance with the applicable Ground Time standards, but sometimes there were still some officers who did not use personal protective equipment such as ear plugs, hand gloves and safety shoes. The obstacles faced by flight coordinator officers are related to supporting facilities, natural and technical factors. The efforts made by flight coordinator officers are to carry out activities according to applicable Ground Time standards.